Implementing Project-Based Learning (PjBL) in Improving EFL Students’ Collaborative Writing in Composing Analytical Exposition Texts: A Classroom Action Research - Herawati, Herawati; Riyanti, Dwi; Novita, Dewi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Collaboration is important skills in English education and it is essential for educators to develop students' potential. This study aims to improve students' collaboration through Project-based Learning (PJBL) on Analytical Exposition Text. This research was conducted at SMA Muhammadiyah 1 Pontianak from September to October 2025, involving 30 students of class XI and using a class action research method with a qualitative approach. Data were collected through observation checklists, field notes, and interview. In Cycle 1, most groups demonstrated improvement in understanding; however, contribution and regulation still required frequent teacher intervention. Some groups achieved success by fulfilling at least two of the three aspects, indicating that collaboration was emerging but not yet consistent. In Cycle 2, significant improvement was observed across all groups. Students showed clearer shared understanding of the task, more balanced contribution among group members, and better self-regulation with minimal teacher support. All groups successfully achieved the three aspects of collaboration, indicating that Project Based Learning effectively fostered collaborative skills in writing analytical exposition texts. The findings suggest that Project Based Learning provides meaningful opportunities for students to engage in collaborative writing processes and supports the development of essential collaboration skills in EFL classrooms. Therefore, PjBL can be considered an effective instructional approach to improve students’ collaboration in writing analytical exposition texts.